1970
DOI: 10.1097/00006254-197009000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Amniotic Fluid Cells; Prenatal Sex Prediction and Culture

Abstract: , 1970, 1, 523-526 Summary: Sex chromatin studies were carried out on small amounts of amniotic fluid obtained by amniocentesis or from intact amniotic sacs removed at hysterotomy. Provided that satisfactory preparations were obtained the accuracy of fetal sexing was 87%. Nevertheless, in the management of a pregnancy in which there is a risk of a serious X-linked recessive disorder, repeat amniocentesis may be necessary to ensure satisfactory specimens.Of 90 samples of fluid cultured, satisfactory growth w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

1972
1972
1972
1972

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
1
0
1
Order By: Relevance
“…-Harvesting is made when the cells are in fewer than 2000 viable cells per ml of amniotic fluid before the 15th week, but Nelson & Emery (1970), comparing cases taken before and after the 20th week, could show no clear relationship between numbers of inoculated cells or gestational age and the success of cell culture. Gerbie et al (1971) and Valenti & Kehaty (1969) found the 14th and 16th weeks to be the optimum time for amniocentesis.…”
Section: Discussionmentioning
confidence: 99%
“…-Harvesting is made when the cells are in fewer than 2000 viable cells per ml of amniotic fluid before the 15th week, but Nelson & Emery (1970), comparing cases taken before and after the 20th week, could show no clear relationship between numbers of inoculated cells or gestational age and the success of cell culture. Gerbie et al (1971) and Valenti & Kehaty (1969) found the 14th and 16th weeks to be the optimum time for amniocentesis.…”
Section: Discussionmentioning
confidence: 99%
“…O rastreamento para aneuploidias inicia-se nos anos setenta (28)(29)(30) , década em que a avaliação do risco para trissomias é baseada principalmente na idade materna e em antecedentes de fetos com anormalidades cromossômicas (29,(31)(32)(33) . (28) .…”
Section: ___________________1 Introduçãounclassified